The Relationship between Anxiety and the Level of Joint Stiffness in Colles Fracture Patients - Muhammad Ariffudin; Zainab Az Zahra (Universitas Muhammadiyah Yogyakarta, 2020)
Colles fracture is 15% of the whole fracture incidents in adults, and joint stiffness is the most common complication. Anxiety is one of a variety of factors strongly associated with an increased risk of disability and pain intensity in patients with musculoskeletal disorders. This study aims to identify the relationship between anxiety and the level of joint stiffness in Colles fracture patients. This research is an observational analytic study with a cross-sectional design. Data collection was carried out in the physiotherapy of PKU Muhammadiyah Gamping Hospital from March to October 2018 by interview using a questionnaire. Data were analyzed using the Spearman correlation test. The result of the study with 13 respondents showed 9 people (69.2%) did not experience anxiety, one person (7.7%) experienced mild anxiety, one person (7.7%) was in moderate anxiety, and two others were in severe anxiety (15.4%). Meanwhile, in terms of the level of joint stiffness, three people (23.1%) were in mild stiffness, three people (23.1%) were in moderate stiffness, six people (46.2%) were in severe stiffness, and one person (7.7%) was in highly severe stiffness. Statistical test of the relationship between anxiety and the level of joint stiffness in patients with Colles fracture showed no significant correlation (p=0.808). It can be concluded that there was no relationship between anxiety and the level of joint stiffness in fracture patients.